2016
DOI: 10.1007/s10815-016-0812-3
|View full text |Cite
|
Sign up to set email alerts
|

Testicular histology may predict the successful sperm retrieval in patients with non-obstructive azoospermia undergoing conventional TESE: a diagnostic accuracy study

Abstract: Purpose The present study sought to determine the diagnostic accuracy of FSH level, testicular volume, and testicular histology in predicting the successful sperm retrieval (SSR) in a large cohort of patients with non-obstructive azoospermia undergoing conventional testicular sperm extraction (TESE). Methods We retrospectively evaluated 356 patients with nonobstructive azoospermia between June 2004 and July 2009. Binary logistic regression was used to evaluate the diagnostic accuracy of our predicting model, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 23 publications
6
30
0
2
Order By: Relevance
“…Our outcomes are consistent with previous studies showing the superiority of mTESE over cTESE in SR outcomes for SCOS men (4,6). Similarly, the significant association between both SCOS and MA and sperm retrieval failure has been previously reported (6,19). It can be concluded that progressively worse histological patterns are associated with lower retrieval results.…”
Section: Discussionsupporting
confidence: 92%
“…Our outcomes are consistent with previous studies showing the superiority of mTESE over cTESE in SR outcomes for SCOS men (4,6). Similarly, the significant association between both SCOS and MA and sperm retrieval failure has been previously reported (6,19). It can be concluded that progressively worse histological patterns are associated with lower retrieval results.…”
Section: Discussionsupporting
confidence: 92%
“…The criteria for the diagnosis of NOA were similar to those applied in a previous study from our group (Caroppo et al ., ). Briefly, patients were defined to have NOA if semen analysis showed azoospermia without spermatozoa in the pellet, ejaculate volume and pH were higher than 1 mL and 7.2, respectively, and no sign of obstruction of the seminal tract was detected on physical examination, scrotal, and transrectal ultrasound.…”
Section: Methodsmentioning
confidence: 97%
“…Therefore, we considered the chance of sperm recovery as drastically reduced to the minimum, so to recommend at first a heterologous fertilisation, but the patient was particularly motivated to father an own biological child. As widely demonstrated in previous studies (Caroppo et al., ; Seo & Ko, ; Weedin, Bennett, Fenig, Lamb, & Lipshultz, ; Yang et al., ), the histopathological patterns could be considered as a predictive factor of SR. Accordingly, the possibility of SR is higher in patients with hypospermatogenesis compared with patients with MA and SCOS.…”
Section: Discussionmentioning
confidence: 63%
“…Caroppo et al. affirmed that patients with SSR had significantly lower serum FSH level (in mean 16.1 IU/L) and higher testicular volume (8.7 ml) compared with sperm retrieval failure, in which FSH value had an average of 22.4 IU/L and a testis volume had a mean of 7.2 ml (Caroppo et al., ).…”
Section: Discussionmentioning
confidence: 99%